A Review of Current Management of Knee Hemarthrosis in the Non-Hemophilic Population. (December 2021) - Potpally, Nikhil; Rodeo, Scott; So, Paul; Mautner, Ken; Baria, Michael; Malanga, Gerard A
The knee joint is one of the most frequently injured joints in the body, and the resulting injury may often lead to the presence of a bloody effusion, or hemarthrosis. The acute management of this condition can have long-lasting implications, and may ultimately result in the early onset of osteoarthritis in this population. Heme, a breakdown product of erythrocytes, and associated pro-inflammatory mediators, are known to have deleterious interactions with cartilage and synovium. The presence of blood in a joint following injury can precipitate these effects and accelerate the degenerative changes in the joint. Currently, there is no consensus on the optimal management of a traumatic knee joint injury with a hemarthrosis. Nontraumatic hemarthosis, seen most commonly in hemophilia patients, has a set of established guidelines that does not routinely recommend drainage of the joint. This article presents a rationale for joint aspiration to minimize the harmful effects of blood following traumatic hemarthrosis.